Biodiversity Informatics Training Curriculum, version 1.2 - Peterson, A. Townsend; Ingenloff, Kate (Biodiversity Informatics, 2016)
The Biodiversity Informatics Training Curriculum represents an integration of three years of teaching and interaction by many instructors and students in a series of interactions in courses across Africa. Digital videos of these courses--shared openly via YouTube--have been compiled into a first field-wide curriculum, which is presented herein. The compilation is, in effect, a digital textbook covering the entire field of biodiversity informatics.